Koping Religius Lansia di Panti Sosial: Satu bulan Observasi - Wastu Adi Mulyono; Rahmi Setiyani; Tiana Dewi (Journal of Bionursing, 2022)
Elderlies have experienced various life challenges during their life. Therefore, most of them have achieved their maturity in life including their awareness of religious and spirituality. While living in a nursing home that is separated from the family closeness may stimulate stress. Their religious and spiritual maturity may be utilized to cope with their new life challenges. This study was to explore religious coping used among elderlies living in nursing homes. A prospective study design was conducted. Totally, 45 elderlies living in the nursing home were invited into the study. A total sampling technique was applied. The religious coping strategy was investigated using questioner Brief R Cope Bahasa Indonesia version. Results indicated that scores of the positive religious coping are higher than the negative religious coping by 16.77 and 5.75 respectively on the first measurement, and 15.3 and 5.05 respectively on the second measurement. Scores of positive religious copings were higher than the negative religious coping in both measurements. Inconclusion, elderlies living in the nursing home tended to use positive religious coping strategies instead of negative religious coping.